Managing ocean environments in a changing climate sustainability and economic perspectives - Noone, Kevin J.; Diaz, Robert J.; Sumaila, Ussif Rashid (Burlington, MA Elsevier, 2013)
"This chapter provides background information for the scope, purpose and structure of this book. Here, we introduce the main themes that are explored in the book, and provide information that is common to all of them. We discuss the need for taking a holistic view of threats to the global ocean. We also introduce the background and boundary conditions for the economic analysis of the potential savings that could be accrued by acting now to mitigate these threats. We show how this analysis can be useful for decision support in the area of marine policy"--Provided by publisher.
Machine generated contents note: 1. Introduction 2. Ocean Acidification 3. Ocean Warming 4. Hypoxia in the Oceans 5. Sea Level Rise 6. Pollution 7. Overuse of Marine Resources 8. Multiple Stressors: Putting the Pieces Together 9. Planning for surprise 10. Valuing the Ocean environment 11. Pacific Case Study 12. Paths to Sustainable Ocean Resources and Services.
Includes bibliographical references and index.
Keywords: Marine ecology; Marine pollution; Marine resources conservation